Intravenous Propofol Allows Fast Intubation in Neonates and Young Infants Undergoing Major Surgery - Sgrò, Stefania; Morini, Francesco; Bozza, Patrizia; Piersigilli, Fiammetta; Bagolan, Pietro; Picardo, Sergio (Frontiers in Pediatrics, 2019)
Aim of the study: In selected surgical neonates and infants, the rapidity of induction and intubation may represent an important factor for their safety. Propofol is an anesthetic characterized by a rapid onset and fast recovery time that may reduce time of anesthetic induction and improve postanesthetic outcome. Aim of this study was to evaluate the safety and efficacy of anesthesia induction in full-term neonates and young infants after propofol bolus administration. Methods: Retrospective study of all consecutive infants below 6 months of age, undergoing general anaesthesia between 2011 and 2013. Cases that received intravenous propofol bolus to induce anesthesia were compared to cases who received inhaled sevoflurane. Time to reach successful orotracheal intubation (OTI) was measured in seconds. Quality of OTI was defined as “excellent”, “good” and “poor” based on established classification was reported. Hemodynamic parameters as systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), heart rate (HR), and oxygen saturation (SaO2) were collected before OTI (t0), at OTI (t1) and at spontaneous breathing recovery (t2). Main adverse effects were recorded for both groups. Results are median (IQ range) or prevalence; p<0.05 was considered significant. Results: 160 infants were enrolled in the study, 80 received propofol and 80 inhaled sevoflurane. Major surgery (involving organs in the thoracic, abdominal or pelvic cavities) was performed in 64% and 54% of patients in the propofol and sevoflurane group, respectively (p=0.07). Patients in the propofol group showed shorter time for OTI [11.5 (4.0-65) versus 360.0 (228.0-720.0) seconds, (p<0.0001)]. No difference was found in the quality of OTI between the two groups. No significant complications were recorded in either group. Conclusions: Propofol is a safe and effective anesthetic in neonates and infants permitting rapid induction of anesthesia and rapid intubation, without negative impact on the quality of intubation and haemodynamic compromise.